1991
DOI: 10.1177/0310057x9101900107
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Rectal Indomethacin with Placebo for Pain Relief following Spinal Surgery

Abstract: Rectal indomethacin was compared with placebo in a randomised, double-blind study of 100 patients undergoing spinal surgery, in which postoperative pain scores, pethidine, diazepam and metoclopramide consumption, bleeding time, blood loss and oral fluid and food tolerance were measured. Side-effects of indomethacin and pethidine were compared in the two groups. In the indomethacin group, pain scores were significantly less for all measurements made during the first three postoperative days, pethidine and diaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Also, because administration of the drugs was continued after the surgery, the preventive effect on postoperative pain was not a reliable finding. [13][14][15][16][17][18] In addition, the rectal route has been underused in adults in the perianesthesia setting; yet it is an excellent option for the patients, because so many are unable to take oral medications. Also, although the reduced availability of parenteral nonopioids should be considered, parenteral nonopioids are more expensive and have a higher rate of complication, and many surgeons refuse to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because administration of the drugs was continued after the surgery, the preventive effect on postoperative pain was not a reliable finding. [13][14][15][16][17][18] In addition, the rectal route has been underused in adults in the perianesthesia setting; yet it is an excellent option for the patients, because so many are unable to take oral medications. Also, although the reduced availability of parenteral nonopioids should be considered, parenteral nonopioids are more expensive and have a higher rate of complication, and many surgeons refuse to use them.…”
Section: Discussionmentioning
confidence: 99%
“…46 Whereas indomethacin suppositories were associated with less dyspepsia and an earlier tolerance of solid food, they increased the incidence of diarrhea. 50 Importantly, none of the trials reported increased bleeding.…”
Section: Analgesic Consumptionmentioning
confidence: 99%
“…A variety of compounds were used. One trial did not specify the type of analgesic, 38 2 used piritramide, 31,37 1 used pethidine, 50 and the remainder used morphine for rescue analgesia or converted the opioids used to morphine equivalents. 29,32Y35,41,42,44Y48,51 Of the 13 trials that analyzed cumulative morphine consumption at 24 hrs, only 6 reported reduced morphine consumption in patients receiving NSAIDs.…”
Section: Analgesic Consumptionmentioning
confidence: 99%
See 2 more Smart Citations